Passive seismic data processing methods to identify contrast intrasalt interlayers in the geological section of the Astrakhan Arch - E. V. Biryaltsev; A. A. Vikhoreva; V. A. Zakharchuk; A. Yu. Komarov; V. V. Pykhalov; O. V. Tinakin (Georesursy, 2024)
The article examines the problem of processing microseismic noise (MN) to identify and evaluate occurrence depth of contrasting geological objects – intersalt interlayers with a potentially high formation pressure. If it is impossible to use artificial wave sources, statistic processing of passive seismic data becomes critical. Due to the accumulation of power spectral density (PSD) during a long-term recording of MN the deterministic medium effect on a random signal spectrum is identified. PSD modulation when the surface or the bottom of the layered medium is exposed to white noise is expressed in terms of the Green’s function (GF) of a wave equation. Relevant GF variations corresponding to the layers form the basis for accumulated PSD approximation, and indicate the depth and contrast of the target features.